Hardening of the Attitudes: Americans' Views on the Death Penalty - Ellsworth, Phoebe C. (1994)
American support for the death penalty has steadily increased since 1966, when opponents outnumbered supporters, and now in the mid-1990s is at a near record high. Research over the last 20 years has tended to confirm the hypothesis that most people’s death penalty attitudes (pro or con) are based on emotion rather than information or rational argument. People feel strongly about the death penalty, know little about it, and feel no need to know more. Factual information (e.g., about deterrence and discrimination) is generally irrelevant to people’s attitudes, and they are aware that this is so. Support for the death penalty has risen for most major felonies. Youth is seen as much less of a mitigating factor than it was 35 years ago, but most people still oppose the execution of the mentally retarded. As crime rates have risen despite repeated promises by politicians to “get tough on crime,” the death penalty has become an increasingly prominent issue in electoral politics, suggesting that public opinion should be an issue of central importance for research. We suggest that future research should focus more explicitly on racial attitudes, on comparisons of the death penalty with specijic alternatives, and on the emotional aspects of attitudes toward the death penalty